Implementação de estratégias argumentativas para estudantes do 9º ano do ensino fundamental: ampliando horizontes compreensivos a partir da Análise do Discurso Bakhtiniana - Anelise Gorett Silva (2024)
The inexpressive proficiency rates related to writing of students in the ninth grade of public elementary school aroused great concerns in the research teacher, reverberating in his teaching work and in his pedagogical praxis significant alternatives on how to improve oral and written productions intrinsic to the argumentative sphere. In view of this, this study aims to broaden students' comprehensive horizons from Bakhtinian Discourse Analysis, aiming to develop strategic intervention activities in the oral and written production of these students. For this, the genres of the argumentative sphere: Regulated Debate and Opinion Article, called Opinion Text in this research, were selected based on the didactic sequence of Dolz, Noverraz and Schneuwly (2004). The strategic activities sought to explore these genres to improve the students' communicative potential, enabling them to emerge opinions, make decisions, argue in a consistent and coherent way themes based on critical readings of the world. The activities, centered on the main difficulties related to textual production skills, will be purposeful and students will have the opportunity to develop readings and properly use the discursive linguistic elements and retextualization operations in favor of the acquisition of their argumentative skills, provided by the National Common Curricular Base for the final years of elementary school. The research, of a qualitative nature, follows the Bakhtinian precepts, allowing students to develop oral and written argumentative texts aware of their argumentative patterns and their attitudes towards the information received. With the expectation that students will be heard from the construction of their own ideas through critical arguments, it is expected to contribute to the improvement of public education in the country with results that enable students to express their own world through language and the construction of new knowledge.